مدراء السعادة في البيئة الوظيفية: توجه مستحدث لإرساء نظام اليقظة الاجتماعية في منظمات الأعمال – شركة غوغل نموذجا - بتغة, صونية (جامعة الوادي - University of Eloued, 2022)
The institutional excellence industry is no longer satisfied with the traditional methods of achieving it by business organizations, especially the giant ones, and the search for modern managerial practices has become a strategic imperative that must be relied upon by decision makers in the organizations. Perhaps one of the most important of these practices is the design of new jobs concerned with the most important resource, which is the human resource, whose mission is to work hard to reach the achievement of what is called organizational happiness. Therefore, this study comes to focus on the first and main official responsible for achieving organizational happiness, which is the chief happiness officer as a tool for monitoring and following up the social climate. The study reached the most important result, which is that the chief happiness officer can be considered a key and an essential condition for the success of the social vigil
Chief Happiness Officers at work place: A new trend to establish a social vigilance system in business organizations-GOOGLE as a model
مقال
Keywords: human resources ; organizational happiness ; chief happiness officers ; social vigilance ; google